الحذف في شعر ابن هانئ الأندلسي - قاسم بشرى (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
يتناول هذا البحث الحذف الإسناديّ وما يتعلّق به في شعر ابن هانئ الأندلسي، إذ بدأ بدراسة مواضع الحذف في المسند، فتناول حذف الخبر ودلالاته، ثمّ حذف الفعل، ودرس ثانيا حذف المسند إليه ودلالاته، فبدأنا فدرس حذف المبتدأ، والمفعول به، ثمّ ما يتعلّق بالإسناد كحذف الصفة والتمييز، مكتفياً ببعض الأمثلة لبيان المراد، وكان لضوابط البحث دور في دراسة هذه الحدود معتمدين على مجموعة غير قليلة من المصادر والمراجع، أوّلها شرح ديوان ابن هانئ، وإنّما اعتمدنا الشرح دون الديوان لتعذّر حصولنا على طبعة موثّقة منه، فضلا عن أنّ الشرح احتوى قصائده كلّها دون استثناء، مع ما امتاز به من تحقيق علمي جيّد، وتنظيم دقيق. We studied in this research in the predicative deletion and what it relates to in Ebn Hani Alandalusi’s poetry, we studied first topics of deletion in predicate, so we started to study the deletion of the enunciative and its implications, then delete the verb, and we studied Secondly the deletion of subject and its implications, we started deleting the inchoative, and the object, then with regard to predication, such as deleting adjective and discrimination , and we had enough with some examples to show what required, the controls of the search led us to these limits, depending on a set of more than few of sources and references, the first was explanation of the divan of Ibn Hani, but we have adopted the explanation without the divan as we could not get documented edition, as the explanation contained all of his poems without exception, and characterized by a good scientific investigation and careful organization.